2012
DOI: 10.1016/j.ijdevneu.2012.10.109
|View full text |Cite
|
Sign up to set email alerts
|

Protein and lipid damage in maple syrup urine disease patients: l‐carnitine effect

Abstract: Maple syrup urine disease (MSUD) is an inborn error of metabolism biochemically characterized by elevated levels of the branched chain amino acids (BCAA) leucine, isoleucine, valine and the corresponding branched-chain α-keto acids. This disorder is clinically characterized by ketoacidosis, seizures, coma, psychomotor delay and mental retardation whose pathophysiology is not completely understood. Recent studies have shown that oxidative stress may be involved in neuropathology of MSUD. l-Carnitine (l-Car) pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…The reported mechanisms for the L-carnitine antiperoxidative role include inhibition of xanthine oxidase activity, scavenger action of free radicals, and chelation of the iron required for the generation of hydroxyl radicals [45,46] or by facilitating the fatty acids transport, thereby lowering the availability of lipids for peroxidation [47]. Reinforcing the hypothesis that L-carnitine could prevent lipid peroxidation in HMGA, this same protective effect was observed in other inborn errors of metabolism, such as in phenylketonuria [48], in maple syrup urine disease [24,31], and in disorders of propionate metabolism [28,33].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The reported mechanisms for the L-carnitine antiperoxidative role include inhibition of xanthine oxidase activity, scavenger action of free radicals, and chelation of the iron required for the generation of hydroxyl radicals [45,46] or by facilitating the fatty acids transport, thereby lowering the availability of lipids for peroxidation [47]. Reinforcing the hypothesis that L-carnitine could prevent lipid peroxidation in HMGA, this same protective effect was observed in other inborn errors of metabolism, such as in phenylketonuria [48], in maple syrup urine disease [24,31], and in disorders of propionate metabolism [28,33].…”
Section: Discussionmentioning
confidence: 65%
“…In addition to its role in the energy metabolism, L-carnitine has been used as an important adjuvant for the therapy of patients with some organic acidurias, including HMGA, in an attempt to facilitate the elimination of toxic acyl groups and presumably to replenish the decreased stores of free carnitine, as well as to release CoASH for essential oxidative pathways. Furthermore, antioxidant properties have been demonstrated for L-carnitine in several pathologies, including in some inborn errors of metabolism [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of redox status in cell cultures exposed to the metabolites and in the liver-specific HL-deficient mice model developed by Gauthier et al (2013) would also be of great importance for this purpose. As regards to L-carnitine, it was shown that supplementation of this compound normalized various parameters of oxidative stress in patients with HL deficiency and other inborn errors (Sitta et al 2009;Mescka et al 2013;dos Santos et al 2015;Guerreiro et al 2015). This beneficial effect could be due to its capacity to remove toxic metabolites and/or its antioxidant properties, signalizing the potential use of this compound as an adjuvant therapy for these inherited metabolic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports showing improvement after L-carnitine therapy in patients with some organic acidemias, including propionic acidemia, methylmalonic acidemia, and glutaric acidemia type I [71–75]. More recent reports have demonstrated that L-carnitine supplementation as adjuvant therapy contributes to the amelioration of blood markers of oxidative damage in patients affected by phenylketonuria [76], maple syrup urine disease [77], and disorders of propionate metabolism [78]. …”
Section: Neuroprotection Afforded By L-carnitine Supplementation In Pmentioning
confidence: 99%